Birth Outcomes for Planned Home and Licensed Freestanding Birth Center Births in Washington State. Issue 5 (November 2021) - Nethery, Elizabeth; Schummers, Laura; Levine, Audrey; Caughey, Aaron B.; Souter, Vivienne; Gordon, Wendy
Abstract : OBJECTIVE: To describe rates of maternal and perinatal birth outcomes for community births and to compare outcomes by planned place of birth (home vs state-licensed, freestanding birth center) in a Washington State birth cohort, where midwifery practice and integration mirrors international settings. METHODS: We conducted a retrospective cohort study including all births attended by members of a statewide midwifery professional association that were within professional association guidelines and met eligibility criteria for planned birth center birth (term gestation, singleton, vertex fetus with no known fluid abnormalities at term, no prior cesarean birth, no hypertensive disorders, no prepregnancy diabetes), from January 1, 2015 through June 30, 2020. Outcome rates were calculated for all planned community births in the cohort. Estimated relative risks were calculated comparing delivery and perinatal outcomes for planned births at home to state-licensed birth centers, adjusted for parity and other confounders. RESULTS: The study population included 10, 609 births: 40.9% planned home and 59.1% planned birth center births. Intrapartum transfers to hospital were more frequent among nulliparous individuals (30.5%; 95% CI 29.2–31.9) than multiparous individuals (4.2%; 95% CI 3.6–4.6). The cesarean delivery rate was 11.4% (95% CI 10.2–12.3) in nulliparous individuals and 0.87% (95% CI 0.7–1.1) in multiparous individuals. The perinatal mortality rate after the onset of labor (intrapartum and neonatal deaths through 7 days) was 0.57 (95% CI 0.19–1.04) per 1, 000 births. Rates for other adverse outcomes were also low. Compared with planned birth center births, planned home births had similar risks in crude and adjusted analyses. CONCLUSION: Rates of adverse outcomes for this cohort in a U.S. state with well-established and integrated community midwifery were low overall. Birth outcomes were similar for births planned at home or at a state-licensed, freestanding birth center. Abstract : Risks of adverse outcomes in planned home and birth center births were similar; overall, perinatal outcomes were comparable with international settings.